Non-atrophic gastric mucosa is an independently associated factor for superficial non-ampullary duodenal epithelial tumors: a multicenter, matched, case-control study - Azusa Kawasaki; Kunihiro Tsuji; Noriya Uedo; Takashi Kanesaka; Hideaki Miyamoto; Ryosuke Gushima; Yosuke Minoda; Eikichi Ihara; Ryosuke Amano; Kenshi Yao; Yoshihide Naito; Hiroyuki Aoyagi; et al. (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims The etiology of superficial non-ampullary duodenal epithelial tumors (SNADETs) remains unclear. Recent studies have reported conflicting associations between duodenal tumor development and Helicobacter pylori infection or endoscopic gastric mucosal atrophy. As such, the present study aimed to clarify the relationship between SNADETs and H. pylori infection and/or endoscopic gastric mucosal atrophy. Methods This retrospective case-control study reviewed data from 177 consecutive patients with SNADETs who underwent endoscopic or surgical resection at seven institutions in Japan over a three-year period. The prevalence of endoscopic gastric mucosal atrophy and the status of H. pylori infection were compared in 531 sex- and age-matched controls selected from screening endoscopies at two of the seven participating institutions. Results For H. pylori infection, 85 of 177 (48.0%) patients exhibited SNADETs and 112 of 531 (21.1%) control patients were non-infected (p<0.001). Non-atrophic mucosa (C0 to C1) was observed in 96 of 177 (54.2%) patients with SNADETs and 112 of 531 (21.1%) control patients (p<0.001). Conditional logistic regression analysis revealed that non-atrophic gastric mucosa was an independent risk factor for SNADETs (odds ratio, 5.10; 95% confidence interval, 2.44-8.40; p<0.001). Conclusions Non-atrophic gastric mucosa, regardless of H. pylori infection status, was a factor independently associated with SNADETs.